Potential Applications of Advanced Nano/Hydrogels in Biomedicine: Static, Dynamic, Multi‐Stage, and Bioinspired. (9th September 2020) - Ayoubi‐Joshaghani, Mohammad Hosein; Seidi, Khaled; Azizi, Mehdi; Jaymand, Mehdi; Javaheri, Tahereh; Jahanban‐Esfahlan, Rana; Hamblin, Michael R.
Abstract: Novel advanced hydrogels can provide a versatile platform for controlled delivery and release of various cargos, with a myriad of biomedical applications. These gel‐based nanostructures possess good biocompatibility, biodegradability, flexibility, multifunctionality, can respond to internal or external stimuli, and can adapt to their surrounding environment. This new generation of hydrogels is not only capable of serving as targeted drug delivery vehicles, but they can also perform a variety of tasks within living cells and organisms. In this review, advanced hydrogels are classified as static, dynamic, multi‐stage, or bioinspired. They can be used as cell‐free gene expression platforms for gene therapy. Administration of nanogel‐based sprays can act as an immunovaccine priming macrophages toward the M1 phenotype to avoid cancer recurrence following surgery. Nanogels can also serve as a dual biosensing and capture platform for liquid biopsies, and can recognize and remove circulating cancer cells from the blood of cancer patients. Abstract : Potential applications of advanced nano/hydrogels in biomedicine, in particular tissue regeneration and cancer therapy, based on a new classification consisting of static, dynamic, multi‐stage, and bioinspired is presented. Guidelines for specific and general uses of each format as well as those with a chance of translation into the clinic are discussed.